Pengendalian Motor DC Tanpa Sikat Sederhana dengan DSC 16-bit pada Aplikasi EDF - Priyatmadi; Fikra Titan Syifa; Eka Firmansyah (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
Basically, commutation process in a brushless DC motor needs rotor position information. However, to reduce production cost, in some specific applications such as fan or pump, the position sensors are not installed. It is possible to extract the rotor position through observing back emf signal available on the motor terminals. In this paper, implementation of a simple sensorless commutation controller algorithm for a BLDC motor is presented. The algorithm is implemented in a 16-bit digital signal processor (DSC). Experiment has shown that it produces correct timing signal to control BLDC motor from 1280 rpm up to over 3000 rpm.